Situation Analysis of Millennial Da’i Habib Ja'far Al-Hadar on Youtube Social Media - Maulidatus Syahrotin Naqqiyah; Agoes Moh.Moefad; Siti Mutmainnah; Nur Robaniyah (Mediakita, 2023)
The shift in preaching media in line with the development of information and communication technology demands media activists understand the strengths, weaknesses, opportunities, and challenges of preaching in the current digital era. Based on this, this study focuses on analyzing the situation of millennial preacher Habib Ja’far al-Hadar on the social media platform YouTube. This study uses a qualitative descriptive research approach with a digital ethnography approach. The research findings indicate that his strengths include being a Habib, having competent knowledge (credible scholarly certification), having good morals, being polite and humble, and, most importantly, being tech-savvy in the current digital era. His weaknesses include being relatively young, so his “wisdom” may still be considered lacking and not fully representing the Islamic sect he follows. Opportunities for his preaching include the many young people who need an “enjoyable” preaching style, the dominance of new media among millennials who are seeking their identity and God, and the scarcity of preachers who can bring the “mosque” to young people who find it challenging to step into the “mosque.” Finally, the threats to his preaching include the possibility of a negative image due to his association with “lost youths” with careless, liberal, or even atheist attitudes and unorthodox thinking.